A method to capture the large relativistic and solvent effects on the UV-vis spectra of photo-activated metal complexes. Issue 8 (8th February 2023) - Creutzberg, Joel; Hedegård, Erik Donovan
Abstract : We investigate the influence of a water solvent on the electronic spectra of a platinum complex (employed in anti-cancer therapy) with structures from molecular dynamics. We find that both solvent and relativistic effects are essential. Abstract : We have recently developed a method based on relativistic time-dependent density functional theory (TD-DFT) that allows the calculation of electronic spectra in solution (Creutzberg, Hedegård, J. Chem. Theory Comput. 18, 2022, 3671). This method treats the solvent explicitly with a classical, polarizable embedding (PE) description. Furthermore, it employs the complex polarization propagator (CPP) formalism which allows calculations on complexes with a dense population of electronic states (such complexes are known to be problematic for conventional TD-DFT). Here, we employ this method to investigate both the dynamic and electronic effects of the solvent for the excited electronic states of trans-trans-trans -[Pt(N3 )2 (OH)2 (NH3 )2 ] in aqueous solution. This complex decomposes into species harmful to cancer cells under light irradiation. Thus, understanding its photo-physical properties may lead to a more efficient method to battle cancer. We quantify the effect of the underlying structure and dynamics by classical molecular mechanics simulations, refined with a subsequent DFT or semi-empirical optimization on a cluster. Moreover, we quantify the effect of employing different methods to set up the solvated system, e.g., how sensitive the results are to the method used for the refinement, and how large a solvent shell that is required. The electronic solvent effect is always included through a PE potential.